Fatal Caffeine Intoxication: A Series of Eight Cases from 1999 to 20091. Issue 3 (6th February 2014) - Banerjee, Priya; Ali, Zabiullah; Levine, Barry; Fowler, David R.
Abstract Caffeine, 1, 3, 7‐trimethylxanthine, is the most widely consumed legal stimulant. The most potent form is over the counter oral tablets. The estimated average daily adult caffeine consumption is 300 mg. Rarely, serious toxicities such as seizure and cardiac arrhythmias have caused death. Caffeine concentrations of 80 mg/L are considered lethal. Cases investigated over 10 years by the Office of the Chief Medical Examiner for the State of Maryland (OCME) whose cause of death was solely or in combination due to caffeine intoxication were reviewed. A total of eight adult cases were identified consisting of two suicides and six undetermined manners. The average postmortem caffeine concentration was 140.4 mg/L. This is the largest case series reported to date of lethal caffeine intoxication. Large doses of prescription medications and/or over the counter medications were abused. No overdoses were from consumption of caffeine‐containing foods. Comprehensive postmortem toxicological testing should test for caffeine to capture these rare deaths.